2014
DOI: 10.2134/jeq2013.07.0273
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluations on Soil Plant Transfer of Lead from an Urban Garden Soil

Abstract: Lead (Pb) is one of the most common contaminants in urban soils. Gardening in contaminated soils can result in Pb transfer from soil to humans through vegetable consumption and unintentional direct soil ingestion. A field experiment was conducted in 2009 and 2010 in a community urban garden with a soil total Pb concentration of 60 to 300 mg kg−1. The objectives of this study were to evaluate soil–plant transfer of Pb, the effects of incorporation of a leaf compost as a means of reducing Pb concentrations in ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 50 publications
7
118
1
Order By: Relevance
“…Although the use of Pb is strongly restricted today, it still represents a serious risk for human health due to its high persistence in soils (Filippelli and Laidlaw, 2010). Total Pb concentrations in urban gardens worldwide vary widely (e.g., from 60 to > 2,500 mg kg −1 ; Cheng et al, 2011;Attanayake et al, 2014), this is also confirmed in this study, whereby the concentrations ranged between 18.5 and 1,076 mg kg −1 . Nonetheless, the mean value of Pb was relatively low compared to other cities (Table 4).…”
Section: Heavy Metal Assessmentsupporting
confidence: 83%
“…Although the use of Pb is strongly restricted today, it still represents a serious risk for human health due to its high persistence in soils (Filippelli and Laidlaw, 2010). Total Pb concentrations in urban gardens worldwide vary widely (e.g., from 60 to > 2,500 mg kg −1 ; Cheng et al, 2011;Attanayake et al, 2014), this is also confirmed in this study, whereby the concentrations ranged between 18.5 and 1,076 mg kg −1 . Nonetheless, the mean value of Pb was relatively low compared to other cities (Table 4).…”
Section: Heavy Metal Assessmentsupporting
confidence: 83%
“…Research suggests that the uptake of soil lead by vegetable crops may be weak 23,24 . Inhalation or consumption of contaminated soil particles, though, represents another exposure pathway.…”
Section: Hypothesismentioning
confidence: 99%
“…21 Studies suggest that repeated addition of organic matter in large quantities dilutes total Pb concentrations in soils and would therefore be beneficial. [55][56][57]59 However, questions remain about long-term effectiveness as the organic amendments decompose over time. Nanomaterials such as nanoscale zero-valent iron 60, 61 and nanoparticulate apatite [62][63][64] have been used for in situ remediation of many contaminants, but the usefulness for Pb in soil is highly unlikely due to relatively high cost considering the sheer volume of urban soil that has to be treated.…”
Section: In Situ Soil Amendments To Immobilize Pbmentioning
confidence: 99%
“…growing,19,55,[119][120][121][122][123][124] relatively little is known about bioavailability and in situ treatment effectiveness in urban soils at levels that may be relevant for the new BLL values.…”
mentioning
confidence: 99%